2017
DOI: 10.3389/fcimb.2017.00399
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae Challenge Increases Matrix Metalloproteinase-8 Expression in Fallopian Tube Explants

Abstract: Background: Neisseria gonorrhoeae (Ngo) is the etiological agent of gonorrhea, a sexually transmitted infection that initially infects the female lower genital tract. In untreated women, the bacteria can ascend to the upper genital reproductive tract and infect the fallopian tube (FTs), which is associated with salpingitis and can lead to impaired FT function and infertility. The extracellular matrix (ECM) plays an important role in cell migration and differentiation in the female genital tract, and some patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…ROS could trigger the tissue MMP activation and subsequent ECM degradation in the process of human trophoblast invasion [ 34 ] or rupture of fetal membranes, a major cause of preterm birth [ 35 ]. Previous studies have also indicated that MMP3, MMP-9, and TIMP-1 might participate in oviduct remodeling during the menstrual cycle [ 36 ], whereas MMP-8 activity participates in tissue remodeling processes during inflammation to establish successful Gonorrhea infection [ 37 ]. From this perspective, it is not surprising that we found GPx8, a member of the antioxidant enzyme family that degrades H 2 O 2 , in the ECM of the rat oviduct and uterus.…”
Section: Discussionmentioning
confidence: 99%
“…ROS could trigger the tissue MMP activation and subsequent ECM degradation in the process of human trophoblast invasion [ 34 ] or rupture of fetal membranes, a major cause of preterm birth [ 35 ]. Previous studies have also indicated that MMP3, MMP-9, and TIMP-1 might participate in oviduct remodeling during the menstrual cycle [ 36 ], whereas MMP-8 activity participates in tissue remodeling processes during inflammation to establish successful Gonorrhea infection [ 37 ]. From this perspective, it is not surprising that we found GPx8, a member of the antioxidant enzyme family that degrades H 2 O 2 , in the ECM of the rat oviduct and uterus.…”
Section: Discussionmentioning
confidence: 99%
“…NOD agonists promoted downregulation of ADAMTSL4. Other groups have observed MMP-2, -8, and -9 upregulation following N. gonorrhoeae challenge of Fallopian tube epithelia (119,120). In contrast, only MMP-2 and -9 are implicated in C. trachomatis mediated Fallopian tube damage.…”
Section: Discussionmentioning
confidence: 94%
“…During gonococcal infection of fallopian tube epithelial cells, MMP2 accumulates intracellularly while MMP9 secretion is increased (MMP3 and MMP8 levels are unchanged) ( 58 ). In fallopian tube explants, MMP8 expression is increased following GC infection, while transcription of MMP3 and MMP9 (as well as the TIMP metallopeptidase inhibitor 1, TIMP-1) are unchanged ( 59 ). The functions and localization of MMPs, when coupled with data indicating their induction during fallopian tube infection, makes these enzymes prime candidates for mechanistic involvement in epithelial damage.…”
Section: Invading the Fallopian Tubementioning
confidence: 99%